Serum bile acids concentration in captive black-tailed prairie dogs (Cynomys ludovicianus). (January 2016) - Wyre, N.; Eshar, D.
Abstract This study was conducted in order to determine serum bile acids concentration in captive black-tailed prairie dogs (Cynomys ludovicianus ). Sixteen healthy intact prairie dogs of both sexes were studied as part of an overall clinical health evaluation performed under general isoflurane anesthesia. Each animal underwent a complete physical examination, complete blood count, serum biochemistry, urinalysis, whole body radiology, and cardiographic examination. Blood samples were collected from the Jugular vein and submitted for a serum bile acids analysis. The mean and median serum bile acids concentration for the black-tailed prairie dog in this study was 12.5 μmol/L (min = 2 μmol/L, max = 24 μmol/L). The data presented in this report can promote better physiological understanding and improve clinical management of this rodent species.